Exploring the Effectiveness of Digital Reading Platforms in Developing Reading Comprehension Skills - Lutvia Nur Fitriani; Sunarti (Universitas Lancang Kuning, 2024)
This study investigates the effectiveness of the digital reading platform ReadWorks in improving the reading comprehension skills of high school students. A within-subject design was employed, wherein students experienced two phases of treatment: the use of conventional teaching methods and the application of the ReadWorks platform, with a washout period in between to minimize carryover effects. The research was conducted with second-grade students at SMA Negeri 16 Samarinda, using a standardized reading comprehension test to assess performance. Paired samples t-tests were utilized to analyze the data. The findings revealed a significant improvement in students' reading comprehension scores when using the ReadWorks platform compared to conventional methods. The statistical analysis shows that the p-values for both the experimental group (p = 0.000) and the control group (p = 0.000) are less than the significance level of 0.05, leading to the rejection of the Null Hypothesis (H0) and acceptance of the Alternative Hypothesis (Ha). These results indicates that the ReadWorks platform is effective in enhancing reading comprehension skills among high school students. The study contributes to the growing body of literature advocating for the integration of digital tools in education to improve student learning outcomes.